Parental Involvement and Academic Achievement: A Story of an International School in Sri Lanka - Wedikandage, L.N.P.; Gunawardana, Kumudu (International Journal of Advanced Research, 2021)
This research found out the relationship between parental involvement and academic achievement with a special focus on the secondary level students in an international school in Colombo, Sri Lanka. The main objective of the current research was to find out the significant difference in student achievement among international school students in respect to parent participation in teacher-parent meetings and their help for their child's homework. The selection of the research method was based on the quantitative research approach and the type of methods available within this broad approach. The sample of the study comprised of 542 students, 542 parents, and 35 teachers in an international school in Colombo, Sri Lanka. Data was collected through questionnaires. The findings concluded that (1) there was no significant difference in student achievement among international students with respect to parent education. (2) there was a significant difference in student achievement among students with respect to their parents' participation in the teacher-parent meetings but (3) there was no significant difference between student achievements among students with respect to parental help on student's homework. (4) Teachers inthe International school are strongly agreed: their school offers workshops and provide resourceful information to help families to understand how children learn, their school has a clear understanding of the defined policies for teachers that encourage communication with the parents discussing the curriculum, student achievement, and ways a parent can be involved, their school provides productive professional developers that train them on the value of parents and ways to encourage partnerships between the school and home, their school encourages the use of our Learning Management System that provides classroom resources and items parents can access. their school assists families in guiding students to set academic goals, and monitor and discuss schoolwork at home, their school provides information to families on how to assist students with the skills they need to improve. However, (5) teachers in the school disagreed that their school trains parents on developing home routines, conditions, and environments that support their child's learning respectively.
Keywords: Parental Involvement; Academic Achievement; International Schools